Analisis Perbandingan Kondisi Kerja Operator Sebelum dan Sesudah Penggunaan Alat Penyaringan Ampas Tahu Berbasis Antropometri - Aminatus Saadah; Siti Muhimatul Khoiroh (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
The tofu residue filtering process at UD. Tahu ALD was performed manually, causing bent posture, repetitive hand movements, and musculoskeletal complaints. This study analyzes operator working conditions before and after implementing an anthropometry-based tofu residue filtering device. The respondents were 10 filtering operators. Data were collected through observation, Nordic Body Map (NBM) questionnaires, Rapid Entire Body Assessment (REBA), and process time measurement. The results show that the average NBM score decreased from 35.10 to 12.90, representing a 63.25% reduction. The REBA score decreased from 8, categorized as high risk, to 2, categorized as low risk. The average filtering time decreased from 30.20 minutes to 18.32 minutes per cycle, representing a 39.34% reduction. These results indicate that the proposed device reduced operator complaints, improved working posture, and increased filtering process efficiency